2011
DOI: 10.1111/j.1365-2516.2010.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative burden of haemophilia A and the impact of target joint development on health-related quality of life: results from the ADVATE Post-Authorization Safety Surveillance (PASS) study

Abstract: Studies with haemophilia A (HA) patients have shown burden in health-related quality of life (HRQOL) when compared with general population norms. In the current study, HA patients' SF-36v2 health survey scores were compared with general population norms and to patients with other chronic conditions. The impact of target joints (TJs) on HRQOL was also examined. The sample was a subset of HA patients enrolled in the Post-Authorization Safety Surveillance (PASS) programme: a prospective open-label study in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 28 publications
5
49
2
2
Order By: Relevance
“…The most plausible explanation is that these patients experience frequent bleeding episodes and have joint damage, as evidenced by a median annual bleed rate (ABR) of 14 bleeds per year and one target joints at baseline prior to receiving BAX326. Similar to the previous studies in haemophilia A and B [9,12,13,[18][19][20], our findings also showed that the burden is more pronounced with respect to the physical rather than the mental aspects of HRQoL.…”
Section: Discussionsupporting
confidence: 92%
“…The most plausible explanation is that these patients experience frequent bleeding episodes and have joint damage, as evidenced by a median annual bleed rate (ABR) of 14 bleeds per year and one target joints at baseline prior to receiving BAX326. Similar to the previous studies in haemophilia A and B [9,12,13,[18][19][20], our findings also showed that the burden is more pronounced with respect to the physical rather than the mental aspects of HRQoL.…”
Section: Discussionsupporting
confidence: 92%
“…Age was an important factor across all populations, as the PCS generally decreased over the years. In our study, mean MCS was unchanged at the end of the study (51.5 ± 9.45 compared to 52.4 ± 7.83) but still higher than the US general norms (47.7 ± 0.24) reported by Klamroth et al [29], whereas mean PCS was comparable to baseline (52.5 vs 49.8) and US general norms (50.7 ± 0.23).…”
Section: Discussioncontrasting
confidence: 68%
“…This low variability could be explained by the fact that our subjects were already on a LDDP regimen at study entry, but also by the low number of subjects enrolled in our study. In the Advate PASS study, Klamroth et al assessed HRQoL in HA patients compared to healthy subjects, and to populations with other chronic diseases [29]. In their study, the PCS was reduced in HA (42.3 ± 0.77) compared to age-matched healthy subjects (54.5 ± 0.24) or those with chronic back pain (46.9 ± 0.4), but comparable to subjects with rheumatoid arthritis (43.6 ± 1.89).…”
Section: Discussionmentioning
confidence: 99%
“…OHR-QoL also allows for a shift from traditional medical/dental criteria to assessment and care that focus on a person's social and emotional experience and physical functioning in defining appropriate treatment goals and outcome [2].By this measure, the discrepancy between the patient's wants, needs or demands, and what the patient has, will be determined. [3] Despite numerous reports on general health and quality of life in CBD patients [4][5][6][7][8], to our knowledge, few published studies have assessed the dental health as well as OHR-QoL in CBD, especially in children. [3,9].…”
Section: Introductionmentioning
confidence: 99%